Genome-wide identification and expression analysis of CASPL gene family in Zea mays (L.) - Xue, Baoping; Liang, Zicong; Li, Dongyang; Liu, Yue; Liu, Chang (Frontiers in Plant Science, 2024)
Casparian strip membrane domain proteins like (CASPL), exhibit profound associations with root development, stress responsiveness and mineral element uptake in plants. Nonetheless, a comprehensive bioinformatics analysis of the ZmCASPL gene family in maize remains unreported. In the study, we have identified 47 ZmCASPL members at the whole-genome level, systematically classifying them into six distinct groups. Furthermore, our analysis revealed that the same group of ZmCASPL contains similar gene structures and conserved motifs. Duplication events showed whole genome duplication (WGD) and tandem duplication (TD) contribute to the generation of the ZmCASPL gene family together in maize, but the former plays a more prominent role. Furthermore, we observed that most ZmCASPL genes contain MYB-binding sites (CAACCA), which are associated with the Casparian strip. Utilizing RNA-seq data, we found that ZmCASPL21 and ZmCASPL47 are specifically highly expressed only in the roots. This finding implies that ZmCASPL21 and ZmCASPL47 may be involved in the Casparian strip development. Additionally, RNA-seq analysis illuminated that drought, salt, heat, cold stresses, low nitrogen and phosphorus conditions, as well as pathogen infection, significantly impact the expression patterns of ZmCASPL genes. RT-qPCR revealed that ZmCASPL 5/13/25/44 genes showed different expression patterns under PEG and NaCl treatments. Collectively, these findings provide a robust theoretical foundation for further investigations into the functional roles of the ZmCASPL gene family in maize.